Experiences and outcomes on the use of telemetry to monitor the fetal heart during labour: findings from a mixed methods study. Issue 3 (May 2022) - Watson, Kylie; Mills, Tracey A.; Lavender, Tina
Abstract: Background: Wireless continuous electronic fetal monitoring (CEFM) using telemetry offers potential for increased mobility during labour. United Kingdom national recommendations are that telemetry should be offered to all women having CEFM during labour. There is limited contemporary evidence on experiences of telemetry use or impacts it may have. Aim: To gather in-depth knowledge about the experiences of women and midwives using telemetry, and to assess any impact that its use may have on clinical outcomes, mobility in labour, control or satisfaction. Methods: A convergent parallel mixed-methods study was employed. Grounded theory was adopted for interviews and analysis of 13 midwives, 10 women and 2 partners. Satisfaction, positions during labour and clinical outcome data was analysed from a cohort comparing telemetry (n = 64) with wired CEFM (n = 64). Qualitative and quantitative data were synthesised to give deeper understanding. Findings: Women using telemetry were more mobile and adopted more upright positions during labour. The core category A Sense of Normality encompassed themes of 'Being Free, Being in Control', 'Enabling and Facilitating' and 'Maternity Unit Culture'. Greater mobility resulted in increased feelings of internal and external control and increased perceptions of autonomy, normality and dignity. There was no difference in control or satisfaction between cohort groups. Conclusions: When CEFM is used during labour, telemetry provides an opportunity to improve experience and support physiological capability. The use of telemetry during labour contributes to humanising birth for women who have CEFM and its use places them at the centre and in control of their birth experience.